Front Cover: Kinematic Modeling of Mechanocatalytic Depolymerization of α‐Cellulose and Beechwood (ChemSusChem 3/2018). Issue 3 (5th February 2018) - Kessler, Martin; Woodward, Robert T.; Wong, Narumi; Rinaldi, Roberto
Abstract : The Front Cover illustrates a schematic representation of the mechanical parameters involved in the mechanocatalytic depolymerization of lignocellulosic materials in a ball mill. Owing to the circular jar movement, a ball follows a defined pathway through the milling vial, which allows the estimation of its velocity and, hence, the determination of the kinetic energy transferred to the substrate. This kinematic modeling approach results in an ultimate equation that is primarily dependent on the mill geometry and characteristics, number of the balls, milling time, and rotational speed. In this work, we demonstrate the existence of correlations between the apparent kinetic energy transfer and the yield of water‐soluble products (oligosaccharides and lignin oligomers) depending on the type of (ligno)cellulose substrate employed. More information can be found in the Full Paper by Kessler et al. on page 552 in Issue 3, 2018 (DOI: 10.1002/cssc.201702060 ).